2009
DOI: 10.1111/j.1365-2842.2009.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of manual therapy and exercise directed at the cervical spine on pain and pressure pain sensitivity in patients with myofascial temporomandibular disorders

Abstract: No studies have investigated the effects of the treatments directed at the cervical spine in patients with temporomandibular disorders (TMD). Our aim was to investigate the effects of joint mobilization and exercise directed at the cervical spine on pain intensity and pressure pain sensitivity in the muscles of mastication in patients with TMD. Nineteen patients (14 females), aged 19-57 years, with myofascial TMD were included. All patients received a total of 10 treatment session over a 5-week period (twice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
3
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 47 publications
2
113
3
7
Order By: Relevance
“…Moreover, sustaining the examination repeatedly results not only in decreasing intensity of head pain referral but also in more expeditious resolution. Furthermore, patients presenting with allodynia frequently report that after lessening of their referred pain, the allodynia has decreased or resolved, [24][25][26] perhaps indicating that a pre-existing central sensitization state had diminished.…”
mentioning
confidence: 99%
“…Moreover, sustaining the examination repeatedly results not only in decreasing intensity of head pain referral but also in more expeditious resolution. Furthermore, patients presenting with allodynia frequently report that after lessening of their referred pain, the allodynia has decreased or resolved, [24][25][26] perhaps indicating that a pre-existing central sensitization state had diminished.…”
mentioning
confidence: 99%
“…It is highly likely that functional integration exists between jaw and cervical movements. Only one study by La Touche et al [22] has shown that mobilization of the cervical spine, together with cervical spine exercises, leads to increased pain-free MMO in the long term in a series of patients with TMD. Regarding pain-free MMO in our study, there were significant increases posttreatment in both groups of cervical intervention compared to the education group.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the first study by La Touche et al [22] evaluating the effectiveness of upper cervical mobilization with neck exercises in TMD reported significant effects on PPT of masticatory muscles. However, the lack of a control group in this study does not allow distinction of the actual treatment effect in TMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volunteers must also have a pain score in the masticatory muscles greater than 3 points on the VAS. 23 …”
Section: Inclusion Criteriamentioning
confidence: 99%